2020
DOI: 10.3390/ijms21114163
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Expression of OsPYL/RCAR7, an ABA Receptor Having Low Signaling Activity, Improves Drought Tolerance without Growth Defects in Rice

Abstract: Overexpression of abscisic acid (ABA) receptors has been reported to enhance drought tolerance, but also to cause stunted growth and decreased crop yield. Here, we constructed transgenic rice for all monomeric ABA receptors and observed that only transgenic rice over-expressing OsPYL/RCAR7 showed similar phenotype with wild type, without total yield loss when grown under normal growth condition in a paddy field. Even though transgenic rice over-expressing OsPYL/RCAR7 showed neither an ABA-sensitivity nor an os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 47 publications
2
7
0
Order By: Relevance
“…Ectopic expression of the RCAR family revealed that subfamily II members are particularly suitable for reducing transpiration without imposing a growth penalty in Arabidopsis ( Yang et al., 2016 ; Yang et al., 2019 ). Similar findings are reported for wheat ( Triticum aestivum ), poplar ( Populus x canescens ), and rice ( Oryza sativa ) by overexpressing TaPYL4, PcRCAR9, and OsPYL/RCAR7, which belong to subfamily II receptors ( Mega et al., 2019 ; Papacek et al., 2019 ; Bhatnagar et al., 2020 ). Alternatively, deficiency in PP2Cs contributes to a water-productive trait.…”
Section: Introductionsupporting
confidence: 79%
“…Ectopic expression of the RCAR family revealed that subfamily II members are particularly suitable for reducing transpiration without imposing a growth penalty in Arabidopsis ( Yang et al., 2016 ; Yang et al., 2019 ). Similar findings are reported for wheat ( Triticum aestivum ), poplar ( Populus x canescens ), and rice ( Oryza sativa ) by overexpressing TaPYL4, PcRCAR9, and OsPYL/RCAR7, which belong to subfamily II receptors ( Mega et al., 2019 ; Papacek et al., 2019 ; Bhatnagar et al., 2020 ). Alternatively, deficiency in PP2Cs contributes to a water-productive trait.…”
Section: Introductionsupporting
confidence: 79%
“…To go further into the potential role of the region of cA ancestry in the adaptation of Asian rice to Africa, we analysed the gene content of this region. Out of a total of 46 genes underlying this introgression, OsABP, OsCNGC, OsPP2C55, OsPP2C56, OsPYL/RCAR7, OsPYL/RCAR8, OsPYL7, and Prol-17 have functions directly related to responses to abiotic stresses such as salt stress and water stress (Bhatnagar et al 2020 ; GonzĂĄlez-GuzmĂĄn et al 2014 ; Han et al 2019 ; Macovei et al 2012 ; Macovei and Tuteja 2012 ; Min et al 2020 ; Nawaz et al 2014 ; Rodriguez 1998 ; Singh et al 2014 ; Tian et al 2015 ; Xu et al 2015 ; Xue et al 2008 ; Yadav et al 2020 ; You et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most of these pathways are functionally redundant and replaceable, so overexpression of the endogenous genes in any of these 2288 pathways is difficult to cause a significant improvement for tolerant phenotypes (Zhu, 2016). Their transformed lines remain at the testing stage (Hu et al, 2010;Xiang et al, 2017;Bhatnagar et al, 2020;Wang et al, 2020). Moreover, transformation may generate completely new interactions between the transgenes making them function differently from what is expected.…”
Section: Endogenous Proteins Are Regulated In Complex Networkmentioning
confidence: 99%